THE ANALYSIS OF HEALTH WORKERS' SUPPORT AND PERCEIVED HEALTH SERVICES NEEDS FACTORS TO IMPROVE THE USE OF THE CHRONIC DISEASE MANAGEMENT PROGRAM (PROLANIS) IN DIABETIC PATIENTS IN KAMONJI PUBLIC HEALTH CENTER, PALU CITY. - Ashari, Muhammad Rizki; Priska Veina Li; Firmansyah, Firmansyah (Journal of Public Health Science, 2025)
Objectives: This study aimed to determine the relationship between health workers’ support and perceived health services needs with the utilization of Prolanis Programs in diabetes mellitus patients in the Kamonji Public Health Center, Palu City. Methods: The research design used an analytic survey with a cross-sectional design. The respondent in this study is a Diabetes Mellitus patient who is a Prolanis Program participant at the Kamonji Public Health Center, Palu City. The sampling technique applied in this study was simple random sampling. 96 respondents were involved in the samples. Results: The results showed a relationship between the perceived health services need (p = 0.003), and there is no relationship between health workers' support (p = 0.862) with the Prolanis Program utilization. Conclusions: There is a relationship between perceived health services needs and no relationship between health workers’ support with the utilization of the Prolanis Program in Kamonji Public Health Center, Palu City. The Public Health Center is intended to develop Prolanis Standard Operational Procedures, both technical and administrative SOPs, to improve health worker collaboration and communication. Health workers are expected to be more proactive in providing guidance and promotion through education about Prolanis services.